Buyouts and Agglomeration Bonuses in Wildlife Corridor Auctions - Justin Dijk; Erik Ansink; Daan van Soest (Tinbergen Institute, 2017)
We present a general model of bidding behavior in wildlife corridor auctions. Given (i) some spatial configuration of landowners in a landscape, (ii) the landowners' opportunity costs, and (iii) the value of establishing the corridor, our model predicts individual landowners' bids, overall participation rates in the auction, as well as the expected net benefits to the conservation agency. We find that market efficiency of the auction increases in the number of potential corridors. We use simulations to compare a benchmark auction with two policy scenarios in a hypothetical landscape. In one scenario, members of a winning corridor receive an agglomeration bonus. In the other scenario, we buy out a pivotal landowner (one that is part of many potential corridors) prior to the auction. Given equal budgets for the agglomeration bonus and the buyout policy, an agglomeration bonus is less efficient than a buyout for conservation agencies facing low budgets, and vice versa. A risk-averse conservation agency is however always better off using a buyout policy.
Keywords: D44; D85; H57; Q57; 330; Wildlife corridors; procurement auctions; nature conservation